Peran Guru Pendidikan Agama Kristen dalam Pembentukan Karakter Kristiani Siswa di SMA Kristen Abdi Wacana Pontianak - Daniel Eka Pratama (Sekolah Tinggi Teologi Borneo, 2023)
Abstract: This study aims to determine the extent of the role of PAK teachers in the formation of the Christian character of students at Abdi Wacana Christian High School and to find out the application of the formation of Christian character education to students at Abdi Wacana Christian High School Pontianak. This research was conducted on awareness of the importance of the role of Christian Religious Education teachers in the formation of the Christian character of students at Abdi Wacana Christian High School Pontianak. This study uses a qualitative method because this method uses data in the form of words or narratives. The data was taken through interview techniques with respondents who were considered to be able to provide accurate information as needed in this study. The findings of the data obtained from this study are first, the formation of Christian character has been implemented in every class. Second, the school's role in shaping Christian character has been carried out in accordance with the vision and mission, motto and in accordance with the character of Christ, which includes loving, forgiving, caring, humble, patient, sincere, willing to share, obedient, and respect each other. Third, the role of the Christian religious education teacher is very important in the application of the formation of Christian character in accordance with the character of Christ. The Christian religious education teacher at Abdi Wacana Christian High School Pontianak has carried out his role in educating students according to and leading to the character of Christ. This role is carried out by means of Spiritual coaching through worship twice a month, acting and exemplifying attitudes not only as a teacher but also as a friend, motivator, and agent of change for his students.Keywords: Christian Religious Education Teacher, Christian Character FormationAbstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana peran guru PAK dalam pembentukan karakter Kristiani Siswa di SMA Kristen Abdi Wacana dan mengetahui penerapan pembentukan pendidikan karakter Kristiani siswa di SMA Kristen Abdi Wacana Pontianak. Penelitian ini dilakukan atas kesadaran pentingnya peran guru Pendidikan Agama Kristen dalam pembentukan karakter Kristiani siswa di SMA Kristen Abdi Wacana Pontianak. Penelitian ini menggunakan metode kualitatif karena metode ini menggunakan data yang berupa kata atau narasi. Data tersebut diambil melalui teknik wawancara terhadap responden yang dinilai dapat memberikan informasi yang akurat sebagaimana yang dibutuhkan dalam penelitian ini. Temuan data yang diperoleh dari penelitian ini adalah pertama, pembentukan karakter kristiani sudah diterapkan di setiap kelas. Kedua, peran sekolah dalam membentuk karakter kristiani telah dilaksanakan sesuai dengan visi-misi, motto dan sesuai dengan karakter Kristus, yang mencakup mengasihi, mengampuni, peduli, rendah hati, sabar, tulus hati, mau berbagi, taat, dan saling menghargai.Ketiga, peran guru Pendidikan agama Kristen sangat penting dalam penerapan pembentukan karakter kristen yang sesuai dengan karakter Kristus. Guru Pendidikanagama Kristen di SMA Kristen Abdi Wacana Pontianak telah melakukan perannya dalam mendidik para naradidik sesuai dan mengarah kepada karakter Kristus. Peran tersebut dilakukan dengan cara pembinaan Rohani melalui Ibadah dua kali dalam satu bulan, bertindak dan meneladani sikap-sikap tidak hanya sebagai pengajar tetapi juga sebagai sahabat, motivator, dan agen perubahan bagi naradidiknya.Kata Kunci: Guru Pendidikan Agama Kristen, Pembentukan Karakter Kristiani